2011
DOI: 10.1039/c1sm05827d
|View full text |Cite
|
Sign up to set email alerts
|

Tuneable mechanical properties in low molecular weight gels

Abstract: The mechanical properties of gels are critical to the final targeted applications. Depending on the application, different properties may be required. Here, we show that the mechanical strength and ability to recover of gels formed using a low molecular weight gelator can be controlled by two independent factors (i) the volume fraction of co-solvent (in this case DMSO) in the system and (ii) the temperature cycle used. These differences correlate with the large scale structure of the network that is formed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
117
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(133 citation statements)
references
References 37 publications
16
117
0
Order By: Relevance
“…This clarifies over a period of minutes as the gel forms. Elsewhere, for a related gelator, we have linked this process to the initial formation of micrometersized spherical droplets, 74 which then decrease in concentration as the self-assembled fibers are formed. We have no evidence that the spherical objects are directly transformed to the fibers, although it has been suggested that fibers nucleate at the surface of the spheres for Fmoc-diphenylalanine.…”
Section: Process Of Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…This clarifies over a period of minutes as the gel forms. Elsewhere, for a related gelator, we have linked this process to the initial formation of micrometersized spherical droplets, 74 which then decrease in concentration as the self-assembled fibers are formed. We have no evidence that the spherical objects are directly transformed to the fibers, although it has been suggested that fibers nucleate at the surface of the spheres for Fmoc-diphenylalanine.…”
Section: Process Of Assemblymentioning
confidence: 99%
“…This agrees with our work on other systems gelled by this approach and seems to arise from a nucleation and growth process. 74 The gels formed by addition of calcium salts to a solution of 2NapFF at high pH show significant aligned domains, whereas a more typical cross-linked network is found for the acid-triggered sample. Hence, we can link the rheological properties to the network.…”
mentioning
confidence: 94%
“…They also reported that the increase in turbidity correlated with a phase separation event forming a dispersion of spheres in solution and that the dispersion was unstable, with a fibrous network being formed at the expense of the spheres. 24 Orbach et al also monitored, by spectroscopic analysis, the formation of the Fmoc-amino acid hydrogels through a transition from a turbid solution to a transparent network. 25 In accordance with previous data of Chen et al, the hypothesis emerged that restructuring of the matter occurred, from multiple irregular aggregates possessing dimensions in the range of the visible wavelength into highly ordered structures, causing the optical characteristics of the solution to change.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…A phenylalanine dipeptide formed organogels when it was firstly dissolved in 1,1,1,3,3,3-hexafluoropropanol and then diluted with poor solvent (26). Fmocprotected dipeptides formed hydrogels when first dissolved in DMSO and then diluted with water (27). In both cases, a highly polar solvent had to be used to dissolve the peptide.…”
Section: Solubility and Gel Formation Abilitymentioning
confidence: 99%